2018
DOI: 10.1039/c8sm00381e
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of poly(2-ethyl-2-oxazoline)/tannic acid multilayers into fibers

Abstract: H-Bonded, pH-responsive poly(2-ethyl-2-oxazoline) (PEOX) and tannic acid (TA) multilayers were prepared by layer-by-layer deposition. Free-floating PEOX/TA multilayers were shown to restructure in a pH3 phosphate buffer solution to H-bonded, pH-responsive PEOX/TA fibers. This restructuring was also evident during the growth of multilayers thicker than 15 bilayers (BL). The growth profile of 30 BL-thick films showed a significant decrease in the film thickness from 118 nm to 85 nm between 15 BL and 20 BL, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…[87] Poly(2-ethyl-2-REVIEW 9 oxazoline) can also be used to form LbL thin films through hydrogen bonding with TA. [90] Alternatively, thermodynamically stabilized materials, such as micelles, [91] can be assembled into thin films with phenolic compounds without disruption. Similarly, proteins can be used as an intermediary layer for TA-based LbL films, [92] and it has been demonstrated that TA does not inhibit the enzymatic activity of the incorporated enzymes after film growth.…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…[87] Poly(2-ethyl-2-REVIEW 9 oxazoline) can also be used to form LbL thin films through hydrogen bonding with TA. [90] Alternatively, thermodynamically stabilized materials, such as micelles, [91] can be assembled into thin films with phenolic compounds without disruption. Similarly, proteins can be used as an intermediary layer for TA-based LbL films, [92] and it has been demonstrated that TA does not inhibit the enzymatic activity of the incorporated enzymes after film growth.…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
“…[126] Very recently, fiber-like self-assembled materials were obtained from TA and poly(2-ethyl-2-oxazoline) using a thin film templating approach followed by rearrangement with acidic buffer. [90] Metal-phenolic coordination interactions can also be used to bridge nano-and microstructures to form complex superstructures. [128] For example, nanoparticles and microparticles were separately coated with phenolic films (MPNs or PDA), mixed, and then crosslinked with metal ions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, it has been confirmed that PTX-NP may be a promising oral drug formulation for chemotherapy in vitro and in vivo , as shown in Figure 6A (Le et al, 2018 ). Adatoz et al ( 2018 ) prepared hydrogen-bonded and pH-responsive poly(2-ethyl-2-oxazoline) (PEOX) and TA multilayers by LbL deposition, which can be reassembled into H-bonded pH-responsive PEOX/TA fibers in phosphate buffer solution, pH 3, validating that pH-responsive fiber aggregates have certain application prospects in a variety of biomedical applications from controlled release to sensors. Luo et al ( 2020 ), using silk fibroin (SF) and TA as raw materials, effectively constructed multifunctional hydrogel adhesives with high extensibility (up to 32,000%), real-time self-healing ability, underwater adhesion, sealing, biocompatibility, and antibacterial properties, through the hydrogen bonding of TA and SF chains in water, which has potential applications in medical fields such as tissue adhesives and integrated bioelectronics, as shown in Figure 6B .…”
Section: Development Of Ta Self-assemblymentioning
confidence: 99%
“…Darüber hinaus nahm bei einem gegebenen PVPON‐Molekulargewicht die Permeabilität der TA‐PVPON‐Schichten ab, wenn der Inkubations‐pH‐Wert von 6 auf 9 geändert wurde . Poly(2‐ethyl‐2‐oxazolin) kann auch zur Bildung von LbL‐Dünnschichten durch Wasserstoffbrücken mit TA verwendet werden …”
Section: Dünne Filmeunclassified
“…Andere Makrostrukturen können mit Copolymeren aus Poly( N ‐(4‐Aminophenyl)methacrylamid‐ co ‐polyethylenglykolmonomethylethermethacrylat) erreicht werden, wobei die Funktionalisierung nach der Polymerisation durch Bildung einer Schiffschen Base mit 3,4‐Dihydroxybenzaldehyd die Assemblierung in Lösungsmittelgemischen mit Fe III oder Cu II zu festen Partikeln oder Vesikeln erlaubt (Abbildung b,c) . Erst kürzlich wurden faserartige selbstorganisierte Materialien aus TA und Poly(2‐ethyl‐2‐oxazolin) unter Verwendung einer Dünnschicht‐Templatmethode erhalten, gefolgt von einer Umlagerung in saurem Puffer …”
Section: Partikelunclassified